Minerals and chelated-based manganese fertilization influences the productivity, uptake, and mobilization of manganese in wheat (Triticum aestivum L.) in sandy loam soils - Dhaliwal, Salwinder Singh; Sharma, Vivek; Shukla, Arvind Kumar; Verma, Vibha; Kaur, Manmeet; Alsuhaibani, Amnah Mohammed; Gaber, Ahmed; Singh, Prabhjot; Laing, Alison M.; Hossain, Akbar (Frontiers in Plant Science, 2023)
Limited manganese (Mn) availability in course textured soil results in its deficiency in wheat. Thus, the foliar application of Mn is widely practised in agricultural production to overcome its deficiency. Further, the comparative efficiency of Mn fertilizers may prove beneficial to increase crop yield and reduce the amount of fertilizer application. With this aim, the present study was conducted to compare the efficiency of minerals (MnCO3 and MnSO4) and chelated manganese fertilizer (Mn-EDTA) to enhance the yield, Mn concentration and uptake of wheat. The MnCO3 was applied at two levels (750 and 1250 ml ha-1) and in two stages (25-30 days after sowing and at 35-40 days) and the recommended dose of MnSO4, as well as Mn-EDTA, was applied in other plots. Results showed that the application of Mn resulted in an augmented yield and Mn uptake of wheat. Among different fertilizers, the results of MnSO4 (5596 kg ha-1) for wheat yield were statistically at par with two sprays of MnCO3 at both levels, however, the economic analysis indicated the use of MnSO4 as more economical over MnCO3. Thus, the present study demonstrated that MnCO3 can be used as an alternative to MnSO4 to enhance the wheat crop.